Peran Orang Tua dalam Pendidikan Anak Tunanetra X Tingkat Dasar - Lestari, Kasih Indah; Sopandi, Asep Ahmad (Jurnal Penelitian Pendidikan Khusus, 2021)
This research is based on the problems found in SLB Negeri 1 Ampek Angkek about the role of parents in the education of elementary-level X visually impaired children. This study uses case study research method with research subjects namely blind parents X, class teachers and principals. In this study, data collection was conducted through observation, interview, and documentation studies, which then the data in the analysis, presented and drawn conclusions. The results of this study aim to examine the role of parents in the education of visually impaired children at the elementary level, namely the role of parents as primary educators, advocates, resources, primary educators, and diagnotism. The role of parents in the education of visually impaired children X has been started by parents X since X was a toddler. X's parents also play a role in choosing education and services for X. X's parents also have an important role in the development of X's interests and talents such as providing motivation and facilitating any form of activity that X is interested in.